BIAYA PANEN DAN PASCA PANEN PETANI CENGKEH DI DESA TAMBELANG KECAMATAN MAESAAN KABUPATEN MINAHASA SELATAN (Harvest and Post harvest Costs of Clove Farmers in Tambelang Village, Maesaan Sub-District, Minahasa Selatan District) - Harke Alfian Kolibu; Mex F. L. Sondakh; O. Esry H. Laoh (Jurusan Sosial Ekonomi Pertanian, Fakultas Pertanian Universitas Sam Ratulangi, Manado, 2023)
This study aims to determine the costs of harvesting and post-harvest clove farmers in Tambelang Village, Maesaan District, South Minahasa Regency. This research was carried out for five months from November 2021 to April 2022. The data collection technique used was the simple random sample technique by selecting 18 cloves. The data used in this study were primary and secondary data. Primary data were obtained through direct interviews through a list of questions that had been prepared. Secondary data was collected from the Maesaan District Office in the form of research village profiles, and from the internet via Google searching in the form of journal articles relevant to this research. The analysis used is the analysis of farm income. The results showed that the average land area was 1.1 ha/year/person with an average total harvest cost of Rp. 39,931,907/year. The biggest costs incurred at harvest are an average of Rp. 15,222,222/year for workers from outside the village and an average of Rp. 16,888,889/year for workers from within the village. While the smallest cost at harvest is found in the cost of rope equipment, which is an average of Rp. 132,222/year. Then the post-harvest costs obtained an average total cost of Rp. 13,027,679 / year with the largest cost found in labor costs for drying, which is an average of Rp. 5,226,235/year and the smallest fee is the tax fee, which is an average of Rp. 57,778/year. Of the two costs, the cost at harvest is the most expensive. The total total cost of harvesting and post-harvesting cloves in Tambelang Village, Maesaan District, South Minahasa Regency, on average, is Rp. 52,904,475/yearth a income is Rp . 33.962.773.